Bioelectrode composition, bioelectrode, method for producing bioelectrode and reaction complex

By using the combination of ionic polymer materials and carbon particle reaction complex and adhesive resin in the biological electrode, a stable biological contact layer is formed, and the problems of conductivity changes and skin allergies in the prior art are solved, and the problem of Efficient and low-cost electrical signal transmission of biological electrodes.

CN114431866BActive Publication Date: 2024-12-13SHIN ETSU CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111299103.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-05
Filing Date
2021-11-04
Publication Date
2024-12-13
Estimated Expiration
2041-11-04

AI Technical Summary

Technical Problem

The existing biological electrodes have large electrical conductivity changes during long-term use, which can easily lead to skin allergies, and it is difficult to maintain stable electrical signal transmission.

Method used

Using a biological electrode composition containing a reaction complex of ionic polymer materials and carbon particles, a biological contact layer with excellent conductivity and biological suitability is formed by combining it with an adhesive resin and a conductive powder to ensure electrical conductivity. No significant drop when the water is wet or dry.

Benefits of technology

It achieves a balance between conductivity and biological fitness, ensures long-term stable electrical signal transmission, reduces the risk of skin allergies, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114431866B_ABST
    Figure CN114431866B_ABST
Patent Text Reader

Abstract

The present invention relates to a bioelectrode composition, a bioelectrode, a method for manufacturing a bioelectrode, and a reaction complex. The present invention provides a bioelectrode composition that can form a biocontact layer for a bioelectrode that has excellent conductivity and biocompatibility, is lightweight, can be manufactured at low cost, and does not significantly reduce conductivity even when wetted or dried, a bioelectrode having a biocontact layer formed by the bioelectrode composition, and a method for manufacturing the same. A bioelectrode composition comprises (A) a reaction complex of an ionic polymer material and carbon particles, wherein the aforementioned (A) component comprises: carbon particles bonded to a polymer having a repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt, or silver salt selected from fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biological electrode that contacts the skin of a living body and can detect body conditions such as heart rate by using electrical signals from the skin, a method for manufacturing the same, and a biological electrode composition suitable for the biological electrode. [Background technology]

[0002] In recent years, with the popularization of IoT (Internet of Things), the development of wearable devices has also progressed. Clocks and glasses that can be connected to the Internet are representative examples. In addition, in the medical field and sports field, there is also a need for wearable devices that can monitor the body's condition at any time, which is a field with future growth potential.

[0003] In the medical field, for example, some people are studying wearable devices that monitor the status of body organs by sensing weak currents, such as electrocardiogram measurement, which uses electrical signals to sense heartbeats. Electrocardiogram measurement is performed by installing electrodes coated with conductive paste on the body, but this is a short-term measurement that is only performed once. In contrast, the development of medical wearable devices such as the above aims to develop devices that monitor health status at any time for several weeks. Therefore, biological electrodes used in medical wearable devices are required to have no changes in conductivity and no skin allergies even when used for a long time. In addition, they are also required to be lightweight and able to be manufactured at a low cost.

[0004] There are two types of medical wearable devices: those that are attached to the body and those that are incorporated into clothing. As the type that is attached to the body, a biological electrode using a water-soluble gel containing water and electrolytes made of the above-mentioned conductive paste has been proposed (Patent Document 1). Regarding the water-soluble gel, sodium, potassium, and calcium are contained as electrolytes in a water-soluble polymer for retaining water, and changes in ion concentration from the skin are converted into electricity. On the other hand, as the type that is incorporated into clothing, a method has been proposed in which a cloth having a conductive polymer such as PEDOT-PSS (Poly-3,4-ethylenedioxythiophene-Polystyrenesulfonate) and a silver paste incorporated into the fiber is used as an electrode (Patent Document 2).

[0005] However, when using the above-mentioned water-soluble gel containing water and electrolytes, there is a problem that the conductivity will also disappear when the water disappears due to drying. On the other hand, when using metals with a high tendency to dissociate such as copper, there is a risk of causing skin allergies in some people. When using conductive polymers such as PEDOT-PSS, there is also a risk of causing skin allergies due to the strong acidity of the conductive polymer, and the conductive polymer may peel off from the fiber during washing.

[0006] In addition, metal nanowires, carbon black, and carbon nanotubes have excellent electrical conductivity, so some people have explored using them as electrode materials (Patent Documents 3, 4, 5). Metal nanowires have a high probability of contact between the wires, so a small amount of addition can be energized. However, metal nanowires are fine materials with pointed front ends, so they can cause skin allergies. As mentioned above, even if the material itself does not cause an allergic reaction, it may sometimes cause biocompatibility to deteriorate due to the shape and irritation of the material, and it is difficult to have both conductivity and biocompatibility.

[0007] It is believed that the conductivity of metal films is very high, so they will function as excellent biological electrodes, but this is not necessarily the case. The current released from the skin due to the beating of the heart is not just a weak current, but also sodium ions, potassium ions, and calcium ions. Therefore, the concentration change of ions must be converted into current, but precious metals that are not easy to dissociate are not efficient in converting ions from the skin into current. Therefore, the impedance of biological electrodes using precious metals is high, and the current passing through the skin is high resistance.

[0008] On the other hand, some people have studied batteries that add ionic liquids (Patent Document 6). Ionic liquids have high thermal stability, chemical stability and excellent conductivity, and their application in battery applications is becoming more and more widespread. However, as shown in Patent Document 6, ionic liquids with small molecular weights are soluble in water. Therefore, if biological electrodes to which they are added are used, the ionic liquids will be extracted by sweat from the skin, not only reducing conductivity, but also penetrating into the skin and causing skin roughness.

[0009] In addition, some people have studied batteries using lithium salts of polymer-type sulfonyl imide (Non-Patent Document 1). However, lithium has high ion mobility and can be used in batteries, but it is not a material with biocompatibility. In addition, some people have studied lithium salts of fluorosulfonic acid suspended in polysilicone (Non-Patent Document 2).

[0010] If the biological electrode is separated from the skin, it cannot obtain information from the body. And even if only the contact area changes, the amount of electricity flowing will change, and the baseline of the electrocardiogram (electrical signal) will change. Therefore, in order to obtain stable electrical signals from the body, the biological electrode needs to be in contact with the skin all the time, and its contact area does not change. Therefore, the biological electrode needs to have adhesion. In addition, it also needs to be stretchable and flexible to follow the expansion and contraction of the skin and the bending changes.

[0011] Some people have studied the use of bioelectrodes in which the part that contacts the skin is silver chloride and silver is laminated as the part that conducts with the device. Solid silver chloride has no adhesion to the skin and no elasticity, so the ability to collect biosignals decreases, especially when the human body is moving. Therefore, it is used in the form of a bioelectrode in which a water-soluble gel is laminated between the laminated film of silver chloride and silver and the skin. In this case, the gel will dry and deteriorate.

[0012] It is reported that when carbon black is mixed with epoxy resin, the curing reaction proceeds at a lower temperature than when epoxy resin is used alone. The reason for this is that the crosslinking reaction can proceed at a lower temperature through the reaction between the carboxyl groups on the surface of carbon black and the epoxy groups (Non-Patent Document 3).

[0013] A lithium ion battery using graphene oxide as a conductive auxiliary agent has been reported (Patent Document 7). In this case, graphene oxide is used as a binder to improve the dispersibility and conductivity of a positive electrode material such as lithium cobalt oxide.

[0014] [Prior art literature]

[0015] [Patent Document]

[0016] [Patent Document 1] International Publication No. WO2013-039151

[0017] [Patent Document 2] Japanese Patent Application Publication No. 2015-100673

[0018] [Patent Document 3] Japanese Patent Application Laid-Open No. 5-095924

[0019] [Patent Document 4] Japanese Patent Application Publication No. 2003-225217

[0020] [Patent Document 5] Japanese Patent Application Publication No. 2015-019806

[0021] [Patent Document 6] Japanese Patent Publication No. 2004-527902

[0022] [Patent Document 7] Japanese Patent Application Publication No. 2020-140973

[0023] [Non-patent literature]

[0024] [Non-patent document 1] J. Mater. Chem. A, 2016, 4, p10038-10069

[0025] [Non-patent document 2] J. of the Electrochemical Society, 150 (8) A1090-A1094 (2003)

[0026] [Non-patent document 3] Polymer Thesis Collection Vol.41, No.10, p597-603 (1984) [Summary of the invention]

[0027] [Problems to be solved by the invention]

[0028] In order to solve the above-mentioned problems, the present invention aims to provide a biological electrode composition that can form a biological contact layer for a biological electrode that has excellent conductivity and biocompatibility, is lightweight and can be manufactured at low cost, and whose conductivity does not significantly decrease even when wetted by water or dried, a biological electrode with a biological contact layer formed by the biological electrode composition, and a manufacturing method thereof.

[0029] [Methods for solving problems]

[0030] In order to solve the above problems, the present invention provides a biological electrode composition.

[0031] A reaction complex containing (A) an ionic polymer material and carbon particles,

[0032] The component (A) comprises carbon particles bonded to a polymer having a repeating unit having a structure of any one of ammonium salt, lithium salt, sodium salt, potassium salt and silver salt selected from fluorosulfonic acid, fluorosulfonyl imide and N-carbonylfluorosulfonamide.

[0033] Such a bioelectrode composition can provide a bioelectrode composition that can form a biocontact layer for a bioelectrode that has excellent conductivity and biocompatibility, is lightweight, can be manufactured at low cost, and whose conductivity does not significantly decrease even when wetted or dried.

[0034] Furthermore, the carbon particles are preferably selected from carbon black, carbon nanotubes, graphite, and graphene.

[0035] Such carbon particles can be preferably used.

[0036] Furthermore, the aforementioned repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt or silver salt selected from fluorosulfonic acid, fluorosulfonyl imide and N-carbonyl fluorosulfonamide preferably has a structure represented by any one of the following general formulas (1)-1 to (1)-4.

[0037] [Chemistry 1]

[0038]

[0039] In the formula, Rf 1 and Rf 2 is a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group, Rf 1 and Rf 2When it is an oxygen atom, Rf 1 and Rf 2 It is an oxygen atom bonded to a carbon atom to form a carbonyl group. 3 and Rf 4 is a hydrogen atom, a fluorine atom, or a trifluoromethyl group, Rf 1 ~Rf 4 One or more of them is a fluorine atom or a trifluoromethyl group. 5 , Rf 6 , Rf 7 is a fluorine atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and has at least one fluorine atom. m is an integer of 1 to 4. + The ion is selected from ammonium ion, lithium ion, sodium ion, potassium ion and silver ion.

[0040] Furthermore, the aforementioned repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt or silver salt selected from any one of fluorosulfonic acid, fluorosulfonyl imide and N-carbonyl fluorosulfonamide is preferably selected from one or more of the repeating units a1 to a7 described in the following general formula (2).

[0041] [Chemistry 2]

[0042]

[0043] In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 Each independently represents a single bond, or any of a linear, branched, or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have an ester group or an ether group or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, and R 7 One or two of the hydrogen atoms in X may be substituted by fluorine atoms. 1 , X 2 , X 3 , X 4 , X 6 , and X 7 Each independently represents any one of a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, and an amide group, and X 5 is any one of a single bond, an ether group, and an ester group. Y is an oxygen atom, -NR 19 -Base, R19 is a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and may be 4 m is an integer from 1 to 4. a1, a2, a3, a4, a5, a6 and a7 are 0≤a1≤1.0, 0≤a2≤1.0, 0≤a3≤1.0, 0≤a4≤1.0, 0≤a5≤1.0, 0≤a6≤1.0, 0≤a7≤1.0, and 0<a1+a2+a3+a4+a5+a6+a7≤1.0. + It is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion. 5 , Rf 6 , Rf 7 It is a fluorine atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and has at least one fluorine atom.

[0044] In addition, the aforementioned component (A) preferably contains, in addition to the repeating units of the aforementioned general formula (2), a polymer that reacts with carbon particles, and a repeating unit b1 having an oxirane group or an oxetane group, or a repeating unit b2 having an isocyanate group copolymerized with the following general formula (4), and a composite obtained by reacting with carbon particles is preferred.

[0045] [Chemistry 3]

[0046]

[0047] In the formula, R 20 , R 24 is a hydrogen atom or a methyl group, X 8 is any one of a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, and an amide group, and X 9 is an ester group, R 21 It is a single bond, a linear, branched, or cyclic alkylene group or a phenylene group having 1 to 20 carbon atoms, and may contain an ether group, an ester group, or a hydroxyl group. 22 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, which may be the same or different. 21 Bond to form a ring. 23 For methylene, ethylene, and can also be 21 Bond and form a ring. 25 It is a linear or branched alkylene group having 1 to 20 carbon atoms and may have an ether group. 26 is a single bond or a methylene group. B is an isocyanate group, and may also be a blocked isocyanate group. 0≤b1<1.0, 0≤b2<1.0, 0<b1+b2<1.0.

[0048] The component (A) is preferably one obtained by reacting 5 parts by mass or more of a polymer reactive with the carbon particles with respect to 100 parts by mass of the carbon particles.

[0049] Furthermore, it is preferred that the component (A) contains an ammonium ion represented by the following general formula (3) as the ammonium ion constituting the ammonium salt.

[0050] [Chemistry 4]

[0051]

[0052] In the formula, R 101d , R 101e , R 101f , R 101g Each is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 13 carbon atoms, a linear, branched, or cyclic alkenyl or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more selected from an ether group, a carbonyl group, an ester group, a hydroxyl group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d With R 101e , R 101d With R 101e With R 101f , or they can form a ring with the nitrogen atom to which they are bonded. When forming a ring, R 101d With R 101e and R 101d With R 101e With R 101f It is an alkylene group having 3 to 10 carbon atoms, or a heteroaromatic ring having a nitrogen atom in the ring.

[0053] If such a biological electrode composition is used, by suspending the carbon particles with an ionic polymer material (hereinafter, the ionic polymer material is also referred to as an ionic polymer), both the ionic conductivity and the electronic conductivity are improved, not only the sensitivity of the biological electrode is better, but also the ionic polymer can be prevented from being extracted outside the biological electrode membrane, thereby preventing the sensitivity of the biological signal from being reduced due to the extraction, reducing the permeability to the skin, and reducing the irritation to the skin, so it is more possible to prevent allergies caused by passing through the skin.

[0054] Furthermore, it is preferred to further contain an adhesive resin as the component (B).

[0055] Furthermore, the component (B) is preferably at least one selected from silicone resins, (meth)acrylate resins, and urethane resins.

[0056] If this is done, it can remain in close contact with the skin and obtain stable electrical signals for a long time.

[0057] In addition, the component (B) preferably contains a diorganosiloxane having an alkenyl group and an organohydrogenpolysiloxane having a SiH group.

[0058] In addition, the component (B) described above preferably further contains a compound having R xSiO (4-x) / 2 Unit (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5.) and SiO 2 The polysilicone resin containing the monomers is preferred.

[0059] If so, it is suitable for use as a biological electrode composition.

[0060] Furthermore, it is preferred to further contain a polymer compound having an ionic repeating unit as the component (C).

[0061] The aforementioned ionic repeating unit of the aforementioned component (C) preferably contains a repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt selected from fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide as described in the following general formula (2).

[0062] [Chemistry 5]

[0063]

[0064] In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 Each independently represents a single bond, or is any of a linear, branched, or cyclic hydrocarbon group having 1 to 13 carbon atoms and may have either an ester group or an ether group or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 One or two of the hydrogen atoms in X may be substituted by fluorine atoms. 1 , X 2 , X 3 , X 4 , X 6 , and X 7 Each independently represents any one of a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, and an amide group, and X 5 is any one of a single bond, an ether group, and an ester group. Y is an oxygen atom, -NR 19 -Base, R 19 is a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and may be 4bond to form a ring. m is an integer from 1 to 4. a1, a2, a3, a4, a5, a6 and a7 are 0≤a1≤1.0, 0≤a2≤1.0, 0≤a3≤1.0, 0≤a4≤1.0, 0≤a5≤1.0, 0≤a6≤1.0, 0≤a7≤1.0, 0<a1+a2+a3+a4+a5+a6+a7≤1.0. M + It is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion. 5 , Rf 6 , Rf 7 It is a fluorine atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and has at least one fluorine atom.

[0065] If the bioelectrode composition contains a polymer compound having such a repeating unit, the effect of the present invention will be further improved.

[0066] Furthermore, it is preferred that the component (D) contains carbon powder and / or metal powder.

[0067] Furthermore, the carbon powder preferably contains at least one of carbon black, graphite and carbon nanotubes.

[0068] Furthermore, the metal powder is preferably a metal powder selected from gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, and indium.

[0069] Furthermore, the aforementioned metal powder is preferably silver powder.

[0070] If this is done, the conductivity will be better.

[0071] Furthermore, it is preferred to further contain an organic solvent as the component (E).

[0072] If so, the coating properties of the biological electrode composition will be better.

[0073] Furthermore, the present invention provides a bioelectrode comprising a conductive substrate and a biocontact layer formed on the conductive substrate, wherein the biocontact layer is a hardened product of the bioelectrode composition.

[0074] The bioelectrode of the present invention has excellent conductivity and biocompatibility, is lightweight, can be manufactured at low cost, and has a conductivity that does not significantly decrease even when wetted or dried.

[0075] Furthermore, the conductive substrate preferably contains one or more selected from the group consisting of gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and a conductive polymer.

[0076] The biological electrode of the present invention is particularly suitable for using such a conductive substrate.

[0077] Furthermore, the present invention provides a method for manufacturing a biological electrode, which is a method for manufacturing a biological electrode having a conductive substrate and a biological contact layer formed on the conductive substrate, by coating the above-mentioned biological electrode composition on the above-mentioned conductive substrate and hardening it to form the above-mentioned biological contact layer.

[0078] According to the method for producing a biological electrode of the present invention, it is possible to easily produce a biological electrode which has excellent conductivity and biocompatibility, is lightweight and can be produced at low cost, and whose conductivity does not significantly decrease even when wetted or dried.

[0079] Furthermore, it is preferred that the method for producing a biological electrode use, for the conductive substrate, one or more materials selected from the group consisting of gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and a conductive polymer.

[0080] The method for producing a biological electrode of the present invention is particularly suitable for using such a conductive substrate.

[0081] In addition, the present invention provides a reaction composite, which is a reaction composite of an ionic polymer material and carbon particles, wherein the aforementioned reaction composite is carbon particles bonded to a polymer, and the polymer has a repeating unit having a structure of any ammonium salt, lithium salt, sodium salt, potassium salt, or silver salt selected from fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide.

[0082] Furthermore, the carbon particles are preferably selected from carbon black, carbon nanotubes, graphite, and graphene.

[0083] Carbon particles modified with ionic polymers are particularly useful as a component of a biological electrode composition that can form a biological contact layer for a biological electrode that can transmit ions and electrical signals released from the skin to a device with high sensitivity and good efficiency (i.e., excellent conductivity), does not cause allergies even if installed on the skin for a long period of time (i.e., excellent biocompatibility), and does not significantly reduce conductivity even if wetted or dried.

[0084] [Effects of the Invention]

[0085] As described above, if the bioelectrode composition contains carbon particles (reaction complex of ionic polymer material and carbon particles) bonded with the ionic polymer of the present invention, it can form a biocontact layer for a bioelectrode that can transmit electrical signals from the skin to the device with good efficiency (i.e., excellent conductivity), has no risk of causing allergies even if installed on the skin for a long period of time (i.e., excellent biocompatibility), is lightweight, can be manufactured at low cost, and has conductivity that does not drop significantly even when wetted or dried. In addition, by adding ionic polymer compounds and conductive powders (carbon powder, metal powder), the conductivity will be better, and by combining with a resin having adhesiveness and elasticity, a bioelectrode with particularly high adhesiveness and high elasticity can be manufactured. In addition, the elasticity and adhesion to the skin can be made better by additives, etc., and the elasticity and adhesion can be adjusted by appropriately adjusting the composition of the resin and the thickness of the biocontact layer.

[0086] Furthermore, the biological electrode of the present invention can achieve both conductivity and biocompatibility through the carbon particles bonded to the ionic polymer, and also has adhesiveness, so the contact area with the skin is constant, and electrical signals from the skin can be stably obtained with high sensitivity.

[0087] Furthermore, according to the method for manufacturing the bioelectrode of the present invention, the bioelectrode of the present invention can be easily manufactured at low cost, which has excellent conductivity and biocompatibility, is lightweight, and has conductivity that does not significantly decrease even when wetted or dried.

Brief Description of the Drawings

[0088] Figure 1 A schematic cross-sectional view showing an example of the biological electrode of the present invention.

[0089] Figure 2 A schematic cross-sectional view showing an example of a biological electrode according to the present invention being installed in a living body.

[0090] Figure 3 A schematic diagram showing a printed biological electrode produced according to an embodiment of the present invention.

[0091] Figure 4 A schematic diagram showing a bioelectrode produced in an embodiment of the present invention is cut out and attached to an adhesive layer.

[0092] Figure 5 A diagram showing the parts where electrodes and ground are attached to the human body when measuring biological signals in an embodiment of the present invention.

[0093] Figure 6 An electrocardiogram waveform obtained using the biological electrode according to the embodiment of the present invention is shown. [Specific implementation method]

[0094] As described above, the present invention seeks to develop a biological electrode composition that can form a biological contact layer for a biological electrode that has high conductivity and excellent biocompatibility for expressing a biological signal with high sensitivity and low noise, is lightweight and can be manufactured at low cost, has no significant decrease in conductivity even when wetted by water or even when dry, and does not leave any residue on the skin after being peeled off from the skin, a biological electrode having a biological contact layer formed by the biological electrode composition, and a manufacturing method thereof.

[0095] In conjunction with the heartbeat, sodium, potassium, and calcium ions are released from the skin surface. The biological electrode needs to convert the increase or decrease of ions released from the skin into an electrical signal. Therefore, a material with excellent ion conductivity is required to transmit the increase or decrease of ions. In conjunction with the heartbeat, the potential on the skin surface also changes. This potential change is very small, and electronic conductivity is also required to transmit weak current to the device.

[0096] Water-soluble gels containing sodium chloride and potassium chloride have high ionic and electronic conductivity, but lose conductivity when the water dries up. Also, sodium chloride and potassium chloride are eluted outside the electrodes in the body during bathing or showering, which can also reduce conductivity.

[0097] Bioelectrodes made of metals such as gold and silver can only detect weak currents, and their ionic conductivity is low, so their sensitivity as bioelectrodes is low. Carbon has electronic conductivity like metals, but its electronic conductivity is lower than that of metals, so its sensitivity as bioelectrodes is lower than that of metals.

[0098] Conductive polymers such as PEDOT-PSS have both electronic conductivity and ionic conductivity, but have low polarization and thus low ionic conductivity.

[0099] The salts of fluorosulfonic acid, fluorosulfonyl imide and N-carbonyl fluorosulfonamide have high polarizability and high ionic conductivity. The purpose of the present invention is to bond them to carbon particles to exhibit high ionic conductivity and electronic conductivity.

[0100] In order to attach to the skin and stably obtain biological signals, the biological electrode film must have adhesiveness. On the other hand, if there is residue on the skin after peeling off after long-term attachment, it is likely to cause rashes and rough skin. In order to prevent the generation of residue, it is considered that the form of an ionic polymer bonded to carbon particles is required, and the present invention is completed.

[0101] The inventors of the present application proposed a bioelectrode composition containing an ionic polymer bonded to carbon particles as a bioelectrode composition, and a bioelectrode obtained by hardening the bioelectrode composition.

[0102] If the acid forming the neutralized salt has high acidity, the ions will be strongly polarized and the ionic conductivity will be improved. For lithium-ion batteries, the lithium salts of bis(trifluoromethanesulfonyl)imidic acid and tris(trifluoromethanesulfonyl)methylated acid show high ionic conductivity for this reason. On the other hand, there is a problem that the higher the acid strength is in the acid state before becoming a neutralized salt, the stronger the biological irritation of the salt. That is, there is a trade-off between ionic conductivity and biological irritation. However, salts used in biological electrodes must take into account both high ionic conductivity and low biological irritation.

[0103] The larger the molecular weight of the ionic compound, the lower the permeability to the skin and the lower the irritation to the skin. Therefore, it is better for the ionic compound to be a high molecular weight polymer. The inventors of the present application thought that: the ionic compound is made into a form with a polymerizable double bond and polymerized into a polymer, and then a reaction complex formed by bonding the polymerized ionic polymer and carbon particles is added, so that no residue is generated even if it is peeled off after being attached to the skin for a long time.

[0104] The inventors of the present application have found that by using this salt system mixed with a silicone-based, acrylic-based, or urethane-based adhesive (resin), it is possible to keep the adhesive in close contact with the skin and obtain a stable electrical signal for a long period of time.

[0105] In order to form a highly sensitive biological electrode, it is important not only to have high ion conductivity but also high electronic conductivity. In order to improve electronic conductivity, it is effective to add metal powder or carbon powder.

[0106] That is, the present invention is a biological electrode composition, comprising (A) a reaction complex of an ionic polymer material and carbon particles,

[0107] The component (A) comprises carbon particles bonded to a polymer having a repeating unit having a structure of any one of ammonium salt, lithium salt, sodium salt, potassium salt and silver salt selected from fluorosulfonic acid, fluorosulfonyl imide and N-carbonylfluorosulfonamide.

[0108] The present invention will be described in detail below, but the present invention is not limited to these.

[0109] <Biological electrode composition>

[0110] The biological electrode composition of the present invention contains (A) a reaction complex of an ionic polymer material and carbon particles, and preferably contains (B) an adhesive resin. Each component is described in more detail below. In addition, hereinafter, the reaction complex of the above-mentioned ionic polymer material and carbon particles is referred to as "(A) component", the adhesive resin is referred to as "(B) component", the mixed ionic polymer is referred to as "(C) component", the conductive powder is referred to as "(D) component", the organic solvent is referred to as "(E) component", and other additives are referred to as "(F) component".

[0111] [(A) Reaction complex (salt) of ionic polymer material and carbon particles]

[0112] In the bioelectrode composition of the present invention, (A) the reaction complex salt of the ionic polymer material and the carbon particles is a carbon particle bonded to a polymer (ionic polymer) having a repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt, or silver salt selected from any one of fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide. Preferably, the polymer further has a repeating unit having an oxirane group or an oxetane group, or an isocyanate group, and is a material in which the polymer is bonded to the carbon particles by reaction.

[0113] The structure of any of the ammonium salt, lithium salt, sodium salt, potassium salt and silver salt of fluorosulfonic acid, fluorosulfonyl imide and N-carbonyl fluorosulfonamide is preferably represented by the following general formula (1)-1 to (1)-4.

[0114] [Chemistry 6]

[0115]

[0116] In the formula, Rf 1 and Rf 2 is a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group, Rf 1 and Rf 2 When it is an oxygen atom, Rf 1 and Rf 2 It is an oxygen atom bonded to a carbon atom to form a carbonyl group. 3 and Rf 4 is a hydrogen atom, a fluorine atom, or a trifluoromethyl group, Rf 1 ~Rf 4 One or more of them is a fluorine atom or a trifluoromethyl group. 5 , Rf 6 , Rf 7 is a fluorine atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and has at least one fluorine atom. m is an integer of 1 to 4. + The ion is selected from ammonium ion, lithium ion, sodium ion, potassium ion and silver ion.

[0117] The above-mentioned repeating units having a structure selected from ammonium salts, lithium salts, sodium salts, potassium salts, silver salts of fluorosulfonic acids represented by general formulas (1)-1 and (1)-2, ammonium salts, lithium salts, sodium salts, potassium salts, silver salts of fluorosulfonyl imide represented by (1)-3, and ammonium salts, lithium salts, sodium salts, potassium salts, silver salts of N-carbonyl fluorosulfonamide represented by (1)-4 are preferably one or more repeating units a1 to a7 selected from the following general formula (2).

[0118] [Chemistry 7]

[0119]

[0120] In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 Each independently represents a single bond, or any of a linear, branched, or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have an ester group or an ether group or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 One or two of the hydrogen atoms in X may be substituted by fluorine atoms. 1 , X 2 , X 3 , X 4 , X 6 , and X 7 Each independently represents any one of a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, and an amide group, and X 5 is any one of a single bond, an ether group, and an ester group. Y is an oxygen atom, -NR 19 -Base, R 19 is a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and may be 4 bond to form a ring. m is an integer from 1 to 4. a1, a2, a3, a4, a5, a6 and a7 are 0≤a1≤1.0, 0≤a2≤1.0, 0≤a3≤1.0, 0≤a4≤1.0, 0≤a5≤1.0, 0≤a6≤1.0, 0≤a7≤1.0, 0<a1+a2+a3+a4+a5+a6+a7≤1.0. M + It is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion. 5 , Rf 6 , Rf 7 It is a fluorine atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and has at least one fluorine atom.

[0121] Specific examples of the fluorosulfonate monomers for obtaining the repeating units a1 to a5 among the repeating units a1 to a7 represented by the general formula (2) include the following.

[0122] [Chemistry 8]

[0123]

[0124] [Chemistry 9]

[0125]

[0126] [Chemistry 10]

[0127]

[0128] [Chemistry 11]

[0129]

[0130] [Chemistry 12]

[0131]

[0132] [Chemistry 13]

[0133]

[0134] [Chemistry 14]

[0135]

[0136] [Chemistry 15]

[0137]

[0138] [Chemistry 16]

[0139]

[0140] [Chemistry 17]

[0141]

[0142] [Chemistry 18]

[0143]

[0144] [Chemistry 19]

[0145]

[0146] [Chemistry 20]

[0147]

[0148] [Chemistry 21]

[0149]

[0150] [Chemistry 22]

[0151]

[0152] [Chemistry 23]

[0153]

[0154] [Chemistry 24]

[0155]

[0156] [Chemistry 25]

[0157]

[0158] [Chemistry 26]

[0159]

[0160] [Chemistry 27]

[0161]

[0162] [Chemistry 28]

[0163]

[0164] Specific examples of the fluorosulfonyl imide salt monomers used to obtain the repeating unit a6 represented by the general formula (2) are as follows.

[0165] [Chemistry 29]

[0166]

[0167] [Chemistry 30]

[0168]

[0169] [Chemistry 31]

[0170]

[0171] [Chemistry 32]

[0172]

[0173] [Chemistry 33]

[0174]

[0175] Specific examples of the N-carbonyl fluorosulfonamide salt monomer used to obtain the repeating unit a7 represented by the general formula (2) include the following.

[0176] [Chemistry 34]

[0177]

[0178] [Chemistry 35]

[0179]

[0180] In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 , and R 13 As mentioned above.

[0181] In the component (A), regarding the ammonium ions constituting the ammonium salt, in particular, M in the repeating unit a (repeating units a1 to a7) + It is preferred that the ammonium ion (ammonium cation) represented by the following general formula (3) be contained.

[0182] [Chemistry 36]

[0183]

[0184] In the formula, R 101d , R 101e , R 101f , R 101g Each is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 13 carbon atoms, a linear, branched, or cyclic alkenyl or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more selected from an ether group, a carbonyl group, an ester group, a hydroxyl group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d With R 101e , R 101d With R 101e With R 101f , or they can form a ring with the nitrogen atom to which they are bonded. When forming a ring, R 101d With R 101e and R 101d With R 101e With R 101f It forms an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having a nitrogen atom in the ring.

[0185] Specific examples of the ammonium ion represented by the general formula (3) include the following.

[0186] [Chemistry 37]

[0187]

[0188] [Chemistry 38]

[0189]

[0190] [Chemistry 39]

[0191]

[0192] [Chemistry 40]

[0193]

[0194] [Chemistry 41]

[0195]

[0196] [Chemistry 42]

[0197]

[0198] [Chemistry 43]

[0199]

[0200] [Chemistry 44]

[0201]

[0202] [Chemistry 45]

[0203]

[0204] [Chemistry 46]

[0205]

[0206] [Chemistry 47]

[0207]

[0208] [Chemistry 48]

[0209]

[0210] [Chemistry 49]

[0211]

[0212] [Chemistry 50]

[0213]

[0214] [Chemistry 51]

[0215]

[0216] [Chemistry 52]

[0217]

[0218] The ammonium ion represented by the general formula (3) is preferably a tertiary or quaternary ammonium ion.

[0219] (Repeating units b1, b2)

[0220] The ionic polymer of the present invention preferably contains, in addition to the aforementioned repeating units a1 to a7, a repeating unit b1 having an oxirane group or an oxetane group or a repeating unit b2 having an isocyanate group represented by the following general formula (4).

[0221] [Chemistry 53]

[0222]

[0223] In the formula, R 20 , R 24 is a hydrogen atom or a methyl group, X 8 is any one of a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, and an amide group, and X 9 is an ester group, R 21 It is a single bond, a linear, branched, or cyclic alkylene group or a phenylene group having 1 to 20 carbon atoms, and may contain an ether group, an ester group, or a hydroxyl group. 22 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, which may be the same or different. 21 Bond to form a ring. 23 For methylene, ethylene, and can also be 21 Bond to form a ring. 25 It is a linear or branched alkylene group having 1 to 20 carbon atoms, and may have an ether group. 26 is a single bond or a methylene group. B is an isocyanate group, and may also be a blocked isocyanate group. 0≤b1<1.0, 0≤b2<1.0, 0<b1+b2<1.0.

[0224] Specific examples of monomers for obtaining the repeating unit b1 represented by the general formula (4) include the following.

[0225] [Chemistry 54]

[0226]

[0227] [Chemistry 55]

[0228]

[0229] Specific examples of monomers for obtaining the repeating unit b2 represented by the general formula (4) include the following.

[0230] [Chemistry 56]

[0231]

[0232] Here, R 20 , R 24 As mentioned above.

[0233] By copolymerizing the repeating units b1 and b2, the repeating units react with the carbon particles to form a composite of the ionomer and carbon.

[0234] (Repeating unit c)

[0235] In the ionic polymer of the component (A) of the biological electrode composition of the present invention, in addition to the above-mentioned repeating units a1 to a7, b1, and b2, a repeating unit c having a glyme chain can be copolymerized to improve conductivity. The monomers used to obtain the repeating unit c having a glyme chain are specifically listed as follows. By copolymerizing the repeating monomer having a glyme chain, when the biological electrode of the present invention is a dry electrode, the movement of ions released from the skin in the dry electrode film can be promoted, and the sensitivity of the dry electrode can be improved.

[0236] [Chemistry 57]

[0237]

[0238] [Chemistry 58]

[0239]

[0240] [Chemistry 59]

[0241]

[0242] [Chemistry 60]

[0243]

[0244] R is a hydrogen atom or a methyl group.

[0245] (Repeating unit d)

[0246] The ionic polymer in the component (A) of the biological electrode composition of the present invention may be copolymerized with a hydrophilic repeating unit d having a hydroxyl group, a carboxyl group, an ammonium salt, a betaine, an amide group, a pyrrolidone, a lactone ring, a lactam ring, a sultone ring, a sodium salt of a sulfonic acid, or a potassium salt of a sulfonic acid in addition to the above-mentioned repeating units a1 to a7, b1, b2, and c in order to improve conductivity. The monomers used to obtain the hydrophilic repeating unit d are specifically listed below. By copolymerizing these repeating units containing hydrophilic groups, the sensitivity of ions released from the skin is improved, and the sensitivity of the dry electrode can be improved.

[0247] [Chemistry 61]

[0248]

[0249] [Chemistry 62]

[0250]

[0251] R is a hydrogen atom or a methyl group.

[0252] (Repeating unit e)

[0253] The ionic polymer in the component (A) of the bioelectrode composition of the present invention may have a repeating unit e that imparts adhesiveness. Specific examples of monomers for obtaining the repeating unit e include the following.

[0254] [Chemistry 63]

[0255]

[0256] [Chemistry 64]

[0257]

[0258] [Chemistry 65]

[0259]

[0260] [Chemistry 66]

[0261]

[0262] [Chemistry 67]

[0263]

[0264] (Repeating unit f)

[0265] The ionic polymer in the component (A) of the bioelectrode composition of the present invention may have a silicon-containing repeating unit f in addition to the repeating units selected from a1 to a7, b1, b2, c to e. The monomers used to obtain the silicon-containing repeating unit f are specifically listed below.

[0266] [Chemistry 68]

[0267]

[0268] n is a number ranging from 0 to 100.

[0269] [Chemistry 69]

[0270]

[0271] (Repeating unit g)

[0272] The ionic polymer in the component (A) of the bioelectrode composition of the present invention has repeating units selected from the above a1 to a7, b1, b2, c to f, and may further have a repeating unit g containing fluorine.

[0273] Specific examples of monomers for obtaining the repeating unit g having fluorine include the following.

[0274] [Chemistry 70]

[0275]

[0276] [Chemistry 71]

[0277]

[0278] [Chemistry 72]

[0279]

[0280] [Chemistry 73]

[0281]

[0282] [Chemistry 74]

[0283]

[0284] [Chemistry 75]

[0285]

[0286] [Chemistry 76]

[0287]

[0288] Here, R is a hydrogen atom or a methyl group.

[0289] As a method for synthesizing the ionic polymer (polymer compound before reacting with carbon particles) in component (A), there is a method in which a desired monomer among monomers providing repeating units a1 to a7, b1, b2, c, d, e, f, and g is added to an organic solvent, a free radical polymerization initiator is added, and the mixture is heated and polymerized to obtain a copolymer polymer compound.

[0290] Examples of organic solvents used in the polymerization include toluene, benzene, tetrahydrofuran, diethyl ether, dioxane, etc. Examples of polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-methylpropionic acid) dimethyl ester, benzoyl peroxide, lauroyl peroxide, etc. The heating temperature is preferably 50 to 80°C, and the reaction time is preferably 2 to 100 hours, more preferably 5 to 20 hours.

[0291] Here, the ratio of the repeating units a1 to a7, b1, b2, c, d, e, f, and g in the ionic polymer in the component (A) is 0≤a1≤1.0, 0≤a2≤1.0, 0≤a3≤1.0, 0≤a4≤1.0, 0≤a5≤1.0, 0≤a6≤1.0, 0≤a7≤1.0, 0<a1+a2+a3+a4+a5+a6+a7≤1.0, 0≤b1<1.0, 0≤b2<1.0、0≤b1+b2<1.0、0≤c<1.0、0≤d<1.0、0≤e<0.9、0≤f<0.9、0≤g<0.9、a1+a2+a3+a4+a5+a6+a7+b1+b2+c+d+e+f+g≤1, preferably 0≤a1≤0.9、0≤a2≤0.9、0≤a3≤0.9、0≤a4≤0.9、0≤a5≤0.9 , 0≤a6≤0.9, 0≤a7≤0.9, 0.01≤a1+a2+a3+a4+a5+a6+a7≤0.99, 0≤b1≤0.8, 0≤b2≤0.8, 0.001≤b1+b2≤0.8, 0≤c≤0.8, 0≤d≤0.8, 0≤e<0.8, 0≤f<0.8, 0≤g<0.8, more preferably 0≤a1≤0.8, 0≤a2≤0.8, 0≤ a3≤0.8, 0≤a4≤0.8, 0≤a5≤0.8, 0≤a6≤0.8, 0≤a7≤0.8, 0.02≤a1+a2+a3+a4+a5+a6+a7≤0.95 , 0≤b1≤0.7, 0≤b2≤0.7, 0.01≤b1+b2≤0.7, 0≤c≤0.7, 0≤d≤0.5, 0≤e<0.3, 0≤f<0.7, 0≤g<0.7.

[0292] Furthermore, when the repeating unit b2 is an unblocked isocyanate, the repeating units b1 and b2 are not present in the same molecule, and b1 and b2 do not react in the polymer molecule, so the reaction with the carbon particles will proceed fully. Therefore, it is better that b1 and b2 are not copolymerized. If the ionic polymer that has been copolymerized with b1 and the ionic polymer that has been copolymerized with b2 are not mixed, b1 and b2 do not react between molecules, so the reaction with the carbon particles will proceed fully, which is more ideal.

[0293] Moreover, for example: a1+a2+a3+a4+a5+a6+a7+b1+b2+c+d+e+f+g=1 means that in a polymer compound containing repeating units a1, a2, a3, a4, a5, a6, a7, b1, b2, c, d, e, f, g, the total amount of the repeating units a1, a2, a3, a4, a5, a6, a7, b1, b2, c, d, e, f, g is 100 relative to the total amount of all the repeating units. In mole %, a1+a2+a3+a4+a5+a6+a7+b1+b2+c+d+e+f+g<1, which means that the total amount of repeating units a1, a2, a3, a4, a5, a6, a7, b1, b2, c, d, e, f, and g relative to the total amount of all repeating units is less than 100 mole %, and there are other repeating units besides a1, a2, a3, a4, a5, a6, a7, b1, b2, c, d, e, f, and g.

[0294] The molecular weight of the ionic polymer in the (A) component is preferably 500 or more, more preferably 1,000 or more and 1,000,000 or less, and even more preferably 2,000 or more and 500,000 or less in terms of weight average molecular weight. In addition, if the amount of ionic monomers (residual monomers) that have not entered the ionic polymer after polymerization is small, there is no risk of penetrating into the skin and causing allergies in the organism, so the amount of residual monomers should be small. The amount of residual monomers is preferably 10 parts by mass or less relative to 100 parts by mass of the ionic polymer in the (A) component. In addition, the ionic polymer can be used alone or in combination of two or more with different molecular weights, dispersities, and polymerization monomers. In addition, the molecular weight (Mw) and dispersity (Mw / Mn) can be confirmed by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.

[0295] Examples of carbon particles include carbon black, carbon nanotubes, graphite, and graphene. Carbon nanotubes and graphene may be single-layer or multi-layer structures. In addition, carbon particles preferably have reactive groups such as hydroxyl, carboxyl, and amino groups.

[0296] When the ionic polymer in the component (A) has an oxirane group, an oxetane group or an isocyanate group, it reacts with the hydroxyl group, the carboxyl group or the amino group on the surface of the carbon particles to form a bond.

[0297] The component (A) is preferably obtained by reacting 5 parts by weight of an ionic polymer with respect to 100 parts by weight of carbon particles. The component (A) is more preferably obtained by reacting 5 parts by weight of a polymer that reacts with carbon particles and is copolymerized with repeating units b1 having an oxirane group or an oxetane group as described in general formula (4), or repeating units b2 having an isocyanate group, with respect to 100 parts by weight of carbon particles.

[0298] By suspending the ionic polymer on the carbon particles, both the ionic conductivity and the electronic conductivity are improved, which not only improves the sensitivity of the biological electrode, but also prevents the ionic polymer from being extracted outside the biological electrode membrane, thereby preventing the sensitivity of the biological signal from decreasing due to the extraction. The permeability to the skin is reduced, and the irritation to the skin is reduced, so it is more possible to prevent allergies caused by passing through the skin.

[0299] When the ionic polymer reacts with the carbon particles, the ionic polymer will be attached to the surface of the carbon particles due to chemical bonding. In the reaction between the ionic polymer and the carbon nanotubes, the ionic polymer will react across a plurality of carbon nanotubes, and sometimes a large gel structure will be formed.

[0300] In order to make the ionic polymer and carbon particles composite, the ionic polymer and carbon particles are mixed and reacted at room temperature or by heating. Heating can be used to promote the reaction, but if the heating temperature is too high, the ionic polymer will decompose, so the heating temperature is preferably below 200°C.

[0301] A catalyst for promoting the reaction may also be added. When the ionic polymer has an oxirane group or an oxetane group and the carbon particles have a carboxyl group, the catalyst may be a metal compound such as pyridine, 2-ethylimidazole, a tertiary amine, zinc 2-ethylhexanoate, or aluminum acetylacetonate. When the ionic polymer has an isocyanate group or a blocked isocyanate group, the reaction may be promoted by adding a tin-based catalyst.

[0302] In the bioelectrode composition of the present invention, the amount of component (A) is preferably 0.1 to 300 parts by mass, more preferably 1 to 200 parts by mass, relative to 100 parts by mass of component (B) described later. Component (A) may be used alone or in combination of two or more.

[0303] The oxirane group, oxetane group, and isocyanate group contained in the ionic polymer are sometimes not completely consumed in the reaction with the carbon particles. In this case, the oxirane group and the oxetane group are coupled with each other, or a diol group is formed by a ring-opening reaction. In this case, the performance as a biological electrode is not reduced, or the irritation to the skin is not enhanced. After reacting with the carbon particles, in order to inactivate the unreacted oxirane group, the oxetane group, and the isocyanate group, it can also be reacted with water, alcohol, or a carboxylic acid compound.

[0304] [(B) Adhesive resin]

[0305] The (B) adhesive resin blended into the biological electrode composition of the present invention is a component for being compatible with the reaction complex (salt) of the above-mentioned (A) ionic polymer material and carbon particles to prevent the salt from eluting, and for fixing the conductivity enhancers such as metal powder, carbon powder, silicon powder, lithium titanate powder, etc. and making them exhibit adhesiveness. When the ionic polymer material in the (A) component has adhesiveness, the (B) adhesive resin is not necessary. In addition, the resin of the (B) component can be any resin other than the above-mentioned (A) component, and it is preferably any one of a thermosetting resin and a photocuring resin, or preferably both of them, and it is particularly preferably one or more resins selected from the group consisting of polysilicone (polysilicone resin), acrylic ((meth)acrylate resin), and carbamate (carbamate resin).

[0306] The adhesive silicone resin may be an addition reaction curing type or a radical crosslinking reaction curing type. For example, the addition reaction curing type may be a diorganosiloxane containing an alkenyl group and an R 3 SiO 0.5 and SiO 2 The free radical crosslinking reaction curing type can use, for example, a diorganopolysiloxane containing an alkenyl group or not, an organohydrogen polysiloxane containing R 3 SiO 0.5 and SiO 2 Here, R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.

[0307] In addition, a polysiloxane / resin one-piece compound formed by condensation reaction of polysiloxane with silanols at the polymer end and side chain and MQ resin can also be used. MQ resin has many silanols, so by adding MQ resin, adhesion can be improved, but there is no crosslinking, so it will not be molecularly bonded with polysiloxane. As mentioned above, by polysiloxane and resin becoming one-piece, adhesion can be increased.

[0308] Furthermore, the polysilicone resin may also be added with a modified siloxane having a group selected from an amino group, an oxirane group, an oxetane group, a polyether group, a hydroxyl group, a carboxyl group, a mercapto group, a methacrylic group, an acrylic group, a phenol group, a silanol group, a carboxylic anhydride group, an aryl group, an aralkyl group, an amide group, an ester group, and a lactone ring. By adding the modified siloxane, the dispersibility of the component (A) in the polysilicone resin is improved. The modified siloxane may be a siloxane having a single end, both ends, or a side chain modified.

[0309] The adhesive acrylic resin may be, for example, one having hydrophilic (meth)acrylate or long-chain hydrophobic (meth)acrylate as repeating units as described in Japanese Patent Application Laid-Open No. 2016-011338. Depending on the situation, (meth)acrylate having a functional group or (meth)acrylate having a siloxane bond may be copolymerized.

[0310] As the adhesive urethane resin, for example, resins having a urethane bond, a polyether bond, a polyester bond, a polycarbonate bond, or a siloxane bond as described in Japanese Patent Application Laid-Open No. 2016-065238 can be used.

[0311] Furthermore, in order to prevent the decrease in conductivity due to the detachment of the component (A) from the biological contact layer, the resin of the component (B) in the biological electrode composition of the present invention is preferably a resin with high compatibility with the above-mentioned component (A). Furthermore, in order to prevent the biological contact layer from peeling off from the conductive substrate, the resin of the component (B) in the biological electrode composition of the present invention is preferably a resin with high adhesion to the conductive substrate. In order to make the resin of the component (B) a resin with high compatibility with the conductive substrate and salt, it is effective to use a resin with high polarity. Such resins include resins having one or more selected from ether bonds, ester bonds, amide bonds, imide bonds, carbamate bonds, thiol bonds, and thiol groups, or polyacrylic resins, polyamide resins, polyimide resins, polyurethane resins, and polythiocarbamate resins. Moreover, on the other hand, the biological contact layer is in contact with the biological body, so it is easily affected by sweat from the biological body. Therefore, in the bioelectrode composition of the present invention, the resin of component (B) is preferably a resin that is highly water-repellent and not easily hydrolyzed. In order to make the resin of component (B) a resin that is highly water-repellent and not easily hydrolyzed, it is effective to use a silicon-containing resin.

[0312] For polyacrylic resins containing silicon atoms, both polymers having polysiloxane in the main chain and polymers having silicon atoms in the side chain can be used ideally. For polymers having polysiloxane in the main chain, siloxane or silsesquioxane having (meth) acrylate propyl groups can be used. In this case, a photo free radical generator can be added to partially polymerize the (meth) acrylate group to harden it.

[0313] The polyamide resin containing silicon atoms may be preferably a polyamide polysilicone resin described in Japanese Patent Application Publication No. 2011-079946 or U.S. Patent No. 5981680. Such a polyamide polysilicone resin may be synthesized by combining, for example, a polysilicone having amino groups at both ends or a non-polysilicone compound having amino groups at both ends, and a non-polysilicone having carboxyl groups at both ends or a polysilicone having carboxyl groups at both ends.

[0314] Alternatively, polyamic acid before cyclization obtained by reacting carboxylic anhydride with amine may be used. Epoxy or oxetane crosslinking agents may be used to crosslink the carboxyl groups of polyamic acid, or esterification reaction of carboxyl groups with hydroxyethyl (meth)acrylate may be performed, followed by photoradical crosslinking of the (meth)acrylate moiety.

[0315] As the polyimide resin containing silicon atoms, for example, polyimide polysilicone resin described in Japanese Patent Application Laid-Open No. 2002-332305 can be preferably used. The viscosity of the polyimide resin is very high, but the viscosity can be reduced by blending a (meth)acrylic monomer as a solvent and a crosslinking agent.

[0316] Polyurethane resins containing silicon atoms include polyurethane polysilicone resins. Such polyurethane polysilicone resins can be crosslinked by using carbamate bonds by mixing and heating a compound having an isocyanate group at both ends and a compound having a hydroxyl group at the end. In this case, it is necessary that either or both of the compound having an isocyanate group at both ends or a compound having a hydroxyl group at the end contain silicon atoms (siloxane bonds). Alternatively, as described in Japanese Patent Publication No. 2005-320418, polysiloxane and carbamate (meth) acrylate monomers are mixed and photocrosslinked. In addition, a polymer having both a siloxane bond and a carbamate bond and having a (meth) acrylate group at the end can be photocrosslinked. In particular, polyurethanes having a main chain with side chains to which silicone chains are attached as described in Japanese Patent Application Laid-Open Nos. 2018-123304 and 2019-70109 are preferred because they have high strength and high elasticity.

[0317] The polythiocarbamate resin containing silicon atoms can be obtained by reacting a compound containing a thiol group with a compound containing an isocyanate group, and any one of these compounds may contain silicon atoms. If a (meth)acrylate group is present at the terminal, it can also be photocured.

[0318] In the polysiloxane resin, the diorganosiloxane having alkenyl groups and R 3 SiO 0.5 and SiO 2 In addition to the MQ resin with units and the organohydrogenpolysiloxane with multiple SiH groups, modified siloxanes having groups selected from amino, oxirane, oxetane, polyether, hydroxyl, carboxyl, mercapto, methacrylate, acrylic, phenol, silanol, carboxylic anhydride, aryl, aralkyl, amide, ester and lactone rings are added, which makes the compatibility with the above-mentioned salts higher.

[0319] A diorganosiloxane having an alkenyl group and an organohydrogenpolysiloxane having a plurality of SiH groups can be cross-linked by an addition reaction using a platinum catalyst.

[0320] For the platinum catalyst, platinum-based catalysts such as chloroplatinic acid, alcohol solutions of chloroplatinic acid, reaction products of chloroplatinic acid and alcohols, reaction products of chloroplatinic acid and olefin compounds, reaction products of chloroplatinic acid and vinyl-containing siloxanes, platinum-olefin complexes, platinum-vinyl-containing siloxane complexes, platinum-based catalysts such as rhodium complexes and ruthenium complexes, etc. can be listed. In addition, these catalysts can also be dissolved / dispersed in alcohol-based, hydrocarbon-based, and siloxane-based solvents for reuse.

[0321] The amount of the platinum catalyst added is preferably in the range of 5 to 2,000 ppm, particularly preferably 10 to 500 ppm, based on 100 parts by mass of the resin of the component (B).

[0322] In the bioelectrode composition of the present invention, the amount of component (B) is preferably 0 to 2000 parts by mass, more preferably 10 to 1000 parts by mass, relative to 100 parts by mass of the reaction complex (A) of the ionic polymer material and the carbon particles. In addition, the components (B) may be used alone or in combination of two or more.

[0323] When an addition-curing silicone resin is used, an addition reaction control agent may be added as a quencher to prevent the platinum catalyst from acting in a solution or in a low-temperature environment before heat curing after the coating is formed. Specific examples thereof include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclohexanol, 3-methyl-3-trimethylsilyloxy-1-butyne, 3-methyl-3-trimethylsilyloxy-1-pentyne, 3,5-dimethyl-3-trimethylsilyloxy-1-hexyne, 1-ethynyl-1-trimethylsilyloxycyclohexane, bis(2,2-dimethyl-3-butynyloxy)dimethylsilane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,1,3,3-tetramethyl-1,3-divinyldisiloxane.

[0324] The amount of the addition reaction control agent added is preferably in the range of 0 to 10 parts by mass, and particularly preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the resin of the component (B).

[0325] Among these, the resin of component (B) preferably contains diorganosiloxane having an alkenyl group and organohydrogenpolysiloxane having a SiH group, and further contains x SiO (4-x) / 2 Unit (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5.) and SiO 2 Polysilicone resins containing 1,2-dimethylformamide are particularly preferred.

[0326] Furthermore, as described later, the biological contact layer is a hardened material of the biological electrode composition. By hardening it, the adhesion of the biological contact layer to both the skin and the conductive substrate becomes good. Furthermore, the hardening means is not particularly limited, and general means can be used, such as heat and light, or both, or a cross-linking reaction using an acid or base catalyst. The cross-linking reaction can be carried out, for example, by appropriately selecting the method described in the Cross-linking Reaction Handbook (Nakayama Yongqing, Maruzen Publishing (2013) Chapter 2 p51~p371).

[0327] [(C) Blending with an ionic polymer]

[0328] In the bioelectrode composition of the present invention, an ionic polymer may be added in addition to the component (A) (blended ionic polymer). The repeating unit of the blended ionic polymer may be the one described in the item of the ionic polymer in the component (A), and in particular, the one represented by the general formula (2) may be used. The amount of the blended ionic polymer added is preferably in the range of 0.1 to 100 parts by mass relative to 100 parts by mass of the resin of the component (B).

[0329] [(D) Conductive powder]

[0330] [Metal powder]

[0331] In the biological electrode composition of the present invention, in order to improve electronic conductivity, metal powder selected from gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, and indium may be added as component (D). The amount of the metal powder added is preferably in the range of 1 to 50 parts by mass relative to 100 parts by mass of the resin of component (B).

[0332] Regarding the types of metal powder, gold, silver, and platinum are ideal from the perspective of conductivity, and silver, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, and chromium are preferred from the perspective of price. From the perspective of biocompatibility, precious metals are ideal, and considering all these factors, silver is the most ideal.

[0333] The shapes of metal powders include spheres, discs, flakes, and needles, but adding flake-shaped powders has the highest conductivity and is more ideal. The size of the metal powder is less than 100 μm and the tap density is 5 g / cm 3 Below, specific surface area 0.5m 2 Chips with a density of / g or more and a low specific surface area are preferred.

[0334] [Toner]

[0335] A carbon material (carbon powder) may be added as a conductivity enhancer. Examples of the carbon material include carbon black, graphite, carbon nanotubes, and carbon fibers. The carbon nanotubes may be single-layer or multi-layer, and the surface may be modified with an organic group. The amount of the carbon material added is preferably in the range of 1 to 50 parts by mass relative to 100 parts by mass of the resin of component (B).

[0336] [Silica powder]

[0337] Silicon powder may also be added to the bioelectrode composition of the present invention in order to improve the ion acceptance sensitivity. Examples of silicon powder include powders of silicon, silicon monoxide, and silicon carbide. The particle size of the powder is not particularly limited, but it is ideally less than 100 μm, and more preferably less than 1 μm. Smaller particles have a large surface area and can accept many ions, thus becoming a highly sensitive bioelectrode. The amount of silicon powder added is preferably in the range of 1 to 50 parts by mass relative to 100 parts by mass of the resin.

[0338] [Lithium titanate powder]

[0339] In order to improve the ion receiving sensitivity, lithium titanate powder may be added to the biological electrode composition of the present invention. Examples of lithium titanate powder include Li 2 TiO 3 、LiTiO 2 , spinel structure Li 4 Ti 5 O 12 Molecular formula, spinel structure products are preferred. In addition, lithium titanate particles composited with carbon can also be used. The particle size of the powder should be less than 100μm, more preferably less than 1μm. Smaller particles have a large surface area and can accept many ions to become highly sensitive biological electrodes. They can also be composite powders with carbon. The amount of lithium titanate powder added is preferably in the range of 1 to 50 parts by mass relative to 100 parts by mass of the resin.

[0340] [(E) Organic solvent]

[0341] In addition, an organic solvent may be added to the biological electrode composition of the present invention as the component (E). Specific examples of the organic solvent include toluene, xylene, isopropylbenzene, 1,2,3-trimethylbenzene, 1,2,4-trimethylbenzene, 1,3,5-trimethylbenzene, styrene, α-methylstyrene, butylbenzene, sec-butylbenzene, isobutylbenzene, isopropyltoluene, diethylbenzene, 2-ethyl-p-xylene, 2-propyltoluene, 3-propyltoluene, 4-propyltoluene, 1,2,3,5-tetramethyltoluene, 1,2,4,5-tetramethyltoluene, tetralin, 4-phenyl-1-butene, tert-amylbenzene, pentylbenzene, 2-tert-butyltoluene, 3-tert-butyltoluene, 4-tert-butyltoluene, 5-isopropyl-m-xylene, 3-methylethylbenzene, tert-butyl-3-ethylbenzene, 4-tert-butyl-o-xylene, 5-tert-butyl-m-xylene, Aromatic hydrocarbon solvents such as toluene, tert-butyl paraxylene, 1,2-diisopropylbenzene, 1,3-diisopropylbenzene, 1,4-diisopropylbenzene, dipropylbenzene, pentamethylbenzene, hexamethylbenzene, hexylbenzene, 1,3,5-triethylbenzene, n-heptane, isoheptane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, 1,6-heptadiene, 5-methyl-1-hexyne, norbornane, norbornene, dicyclopentadiene, 1-methyl-1,4-cyclohexadiene, 1-heptyne, 2-heptyne, cycloheptane, cycloheptene, 1,3-dimethylcyclopentane, ethylcyclopentane, methylcyclohexane, 1-methyl-1-cyclohexene, 3-methyl-1-cyclohexene, methylenecyclohexane, 4-methyl-1-cyclohexene, 2-methyl 1-hexene, 2-methyl-2-hexene, 1-heptene, 2-heptene, 3-heptene, n-octane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, 3,4-dimethylhexane, 3-ethyl-2-methylpentane, 3-ethyl-3-methylpentane, 2-methylheptane, 3-methylheptane, 4-methylheptane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane, cyclooctane, cyclooctene, 1,2-dimethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, ethylcyclohexane, vinylcyclohexane, isopropylcyclopentane, 2,2-dimethyl-3-hexene, 2, 4-dimethyl-1-hexene, 2,5-dimethyl-1-hexene, 2,5-dimethyl-2-hexene, 3,3-dimethyl-1-hexene, 3,4-dimethyl-1-hexene, 4,4-dimethyl-1-hexene, 2-ethyl-1-hexene, 2-methyl-1-heptene, 1-octene, 2-octene, 3-octene, 4-octene, 1,7-octadiene, 1-octyne, 2-octyne, 3-octyne, 4-octyne, n-nonane, 2,3-dimethylheptane, 2,4-dimethylheptane, 2,5-dimethylheptane, 3,3-dimethylheptane, 3,4-dimethylheptane, 3,5-dimethylheptane, 4-ethylheptane, 2-methyloctane, 3-methyloctane, 4-methyloctane, 2,2,4,4-Tetramethylpentane, 2,2,4-Trimethylhexane, 2,2,5-Trimethylhexane, 2,2-Dimethyl-3-heptene, 2,3-Dimethyl-3-heptene, 2,4-Dimethyl-1-heptene, 2,6-Dimethyl-1-heptene, 2,6-Dimethyl-3-heptene, 3,5-Dimethyl-3-heptene, 2,4,4-Trimethyl-1-hexene, 3,5,5-Trimethyl-1-hexene, 1-Ethyl-2-methylcyclohexane, 1-Ethyl-3-methylcyclohexane, 1-Ethyl-4 -methylcyclohexane, propylcyclohexane, isopropylcyclohexane, 1,1,3-trimethylcyclohexane, 1,1,4-trimethylcyclohexane, 1,2,3-trimethylcyclohexane, 1,2,4-trimethylcyclohexane, 1,3,5-trimethylcyclohexane, allylcyclohexane, octahydroindene, 1,8-nonadiene, 1-nonyne, 2-nonyne, 3-nonyne, 4-nonyne, 1-nonene, 2-nonene, 3-nonene, 4-nonene, n-decane, 3,3-dimethyloctane, 3,5-dimethyloctane, 4,4-dimethyloctane Methyloctane, 3-ethyl-3-methylheptane, 2-methylnonane, 3-methylnonane, 4-methylnonane, tert-butylcyclohexane, butylcyclohexane, isobutylcyclohexane, 4-isopropyl-1-methylcyclohexane, pentylcyclopentane, 1,1,3,5-tetramethylcyclohexane, cyclododecane, 1-decene, 2-decene, 3-decene, 4-decene, 5-decene, 1,9-decadiene, decahydronaphthalene, 1-decyne, 2-decyne, 3-decyne, 4-decyne, 5-decyne, 1,5,9-decadiene, 2, 6-dimethyl-2,4,6-octatriene, limonene, myrcene, 1,2,3,4,5-pentamethylcyclopentadiene, α-phellandrene, pinene, terpinene, tetrahydrodicyclopentadiene, 5,6-dihydrodicyclopentadiene, 1,4-decadiyne, 1,5-decadiyne, 1,9-decadiyne, 2,8-decadiyne, 4,6-decadiyne, n-undecane, pentylcyclohexane, 1-undecene, 1,10-undecadiene, 1-undecene, 3-undecene, 5-undecene, tricyclo[6.2.1.0, 2,7] undec-4-ene, n-dodecane, 2-methylundecane, 3-methylundecane, 4-methylundecane, 5-methylundecane, 2,2,4,6,6-pentamethylheptane, 1,3-dimethyladamantane, 1-ethyladamantane, 1,5,9-cyclododecatriene, 1,2,4-trivinylcyclohexane, aliphatic hydrocarbon solvents such as isoalkanes, cyclohexanone, cyclopentanone, 2-octanone, 2-nonanone, 2-heptanone, 3-heptanone, 4-heptanone, 2-hexanone, 3-hexanone, diisobutyl ketone, methylcyclohexanone, methyl-n-amyl ketone and other ketone solvents, 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol and other alcohol solvents, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, Ether solvents such as ethylene glycol monoethyl ether, propylene glycol dimethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monopentyl ether, diethylene glycol monoheptyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, diisopropyl ether, diisobutyl ether, diisopentyl ether, di-n-pentyl ether, methyl cyclopentyl ether, methyl cyclohexyl ether, di-n-butyl ether, di-sec-butyl ether, diisopentyl ether, di-sec-pentyl ether, di-tert-pentyl ether, di-n-hexyl ether, and anisole; ester solvents such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate; lactone solvents such as γ-butyrolactone; and water.

[0342] Moreover, the addition amount of the organic solvent is preferably in the range of 10 to 50,000 parts by mass based on 100 parts by mass of the resin of the component (B).

[0343] [(F) Other additives]

[0344] In the biological electrode composition of the present invention, in addition to the platinum catalyst and addition reaction control agent described in the item of component (B), a crosslinking agent, a crosslinking catalyst, an ionic additive, and silica particles, polyether polysilicone, and polyglycerol polysilicone can also be mixed. The surface of the silica particles is hydrophilic, and has good compatibility with hydrophilic ionic polymers, polyether polysilicone, and polyglycerol polysilicone, which can improve the dispersibility of ionic polymers in hydrophobic silicone adhesives and polyether polysilicone and polyglycerol polysilicone in silicone adhesives. Silica particles can be used ideally in both dry and wet processes.

[0345] [Crosslinking agent]

[0346] An epoxy-based crosslinking agent may also be added to the bioelectrode composition of the present invention. The crosslinking agent in this case is a compound having multiple epoxy groups or oxetane groups in one molecule. The amount added is 1 to 30 parts by mass relative to 100 parts by mass of the resin of component (B).

[0347] [Cross-linking catalyst]

[0348] A catalyst for cross-linking epoxy groups and oxetane groups may also be added to the bioelectrode composition of the present invention. The catalyst in this case may be one described in paragraphs 0027 to 0029 of Japanese Patent Application No. 2019-503406. The amount added is 0.01 to 10 parts by mass relative to 100 parts by mass of the resin of component (B).

[0349] [Ionic additives]

[0350] The biological electrode composition of the present invention may be added with an ionic additive for improving ionic conductivity. If biological compatibility is considered, sodium chloride, potassium chloride, calcium chloride, magnesium chloride, saccharin sodium salt, acesulfame potassium, sodium carboxylate, potassium carboxylate, calcium carboxylate, sodium sulfonate, potassium sulfonate, calcium sulfonate, sodium phosphate, potassium phosphate, calcium phosphate, magnesium phosphate, betaine, and salts disclosed in Japanese Patent Application Laid-Open No. 2018-44147, Japanese Patent Application Laid-Open No. 2018-59050, Japanese Patent Application Laid-Open No. 2018-59052, and Japanese Patent Application Laid-Open No. 2018-130534 may be cited.

[0351] (Polysilicone compound having a polyglycerol structure)

[0352] In the biological electrode composition of the present invention, a polysilicone compound having a polyglycerol structure may be added to improve the moisture retention of the membrane and the sensitivity and ion conductivity of ions released from the skin. The amount of the polysilicone compound having a polyglycerol structure is preferably 0.01 to 100 parts by mass, and more preferably 0.5 to 60 parts by mass, relative to 100 parts by mass of the total of the components (A) and (B). The polysilicone compound having a polyglycerol structure may be used alone or in combination of two or more.

[0353] The polysilicone compound having a polyglycerol structure is preferably represented by the following general formula (4)' and (5)'.

[0354] [Chemistry 77]

[0355]

[0356] In formula (4)' and (5)', R 1 ' are each independent and may be the same or different from each other, and are a hydrogen atom or a linear or branched alkyl group having 1 to 50 carbon atoms, or a phenyl group, and may contain an ether group, or may be a polysiloxane chain represented by the general formula (6)', R 2 ' is a group having a polyglyceryl structure represented by formula (4)'-1 or formula (4)'-2, R 3 ' are independent of each other, may be the same or different from each other, and are the aforementioned R 1'group or the aforementioned R 2 'Group, R 4 ' are independent of each other, may be the same or different, and are the aforementioned R 1 'group, the aforementioned R 2 ' group or oxygen atom. 4 When ' is an oxygen atom, two R 4 The ' group can also be bonded to form an ether group and form a ring with the silicon atom. a' can be the same or different, and is 0 to 100, b' is 0 to 100, and a'+b' is 0 to 200. However, when b' is 0, R 3 At least one of ' is the aforementioned R 2 ' group. In formula (4)'-1 and (4)'-2, (5)', (6)', R 5 ' is an alkylene group having 2 to 10 carbon atoms or an aralkylene group having 7 to 10 carbon atoms, R 6 '、R 7 ' is an alkylene group with 2 to 6 carbon atoms, R 7 ' may be an ether bond, c' is 0-20, and d' is 1-20.

[0357] Examples of such polysilicone compounds having a polyglycerol structure include the following.

[0358] [Chemistry 78]

[0359]

[0360] [Chemistry 79]

[0361]

[0362] [Chemistry 80]

[0363]

[0364] [Chemistry 81]

[0365]

[0366] [Chemistry 82]

[0367]

[0368] [Chemistry 83]

[0369]

[0370] [Chemistry 84]

[0371]

[0372] [Chemistry 85]

[0373]

[0374] [Chemistry 86]

[0375]

[0376] [Chemistry 87]

[0377]

[0378] In the formula, a', b', c' and d' are as described above.

[0379] When such a polysilicone compound having a polyglycerol structure is contained, it is possible to exhibit better moisture retention, and as a result, it is possible to obtain a bioelectrode composition capable of forming a biocontact layer that exhibits better sensitivity to ions released from the skin.

[0380] As described above, the bioelectrode composition of the present invention can form a bioelectrode contact layer for a bioelectrode that can transmit electrical signals from the skin to a device with good efficiency (i.e., excellent conductivity), has no risk of causing allergies even if installed on the skin for a long period of time (i.e., excellent biocompatibility), is lightweight, can be manufactured at low cost, and has a conductivity that does not drop significantly even when wet or dried. Furthermore, by adding conductive powder (carbon powder, metal powder), the conductivity can be made better, and by combining with a resin having adhesiveness and elasticity, a bioelectrode with particularly high adhesiveness and high elasticity can be manufactured. Furthermore, additives can be used to make the elasticity and adhesion to the skin better, and the elasticity and adhesion can be adjusted by appropriately adjusting the composition of the resin and the thickness of the biocontact layer.

[0381] <Biological Electrode>

[0382] Furthermore, the present invention provides a bioelectrode comprising a conductive substrate and a biocontact layer formed on the conductive substrate, wherein the biocontact layer is a cured product of the bioelectrode composition of the present invention.

[0383] The biological electrode of the present invention will be described in detail below with reference to the drawings, but the present invention is not limited to these drawings.

[0384] Figure 1 A schematic cross-sectional view showing an example of the biological electrode of the present invention. Figure 1The bioelectrode 1 comprises: a conductive substrate 2, and a biocontact layer 3 formed on the conductive substrate 2. The biocontact layer 3 is composed of a hardened bioelectrode composition of the present invention. The ionic reaction complex 4 constituting the biocontact layer 3 is a complex of the above-mentioned ionic polymer material and carbon particles (for example, carbon particles modified by the above-mentioned ionic polymer). The biocontact layer 3 may further contain an adhesive resin 6 and a blended ionic polymer 5 in addition to the above-mentioned ionic reaction complex 4. Figure 1 , 2 , the description is made with respect to the case where the biological contact layer 3 is a layer in which the ionic reaction complex 4 and the mixed ionic polymer 5 are dispersed in the adhesive resin 6, but the biological electrode of the present invention is not limited to this aspect.

[0385] Use such Figure 1 When the biological electrode 1 is Figure 2 , the bio-contact layer 3 (i.e., the layer obtained by dispersing the ionic reaction complex 4 and the mixed ionic polymer 5 in the adhesive resin 6) is brought into contact with the bio-body 7, and the electric signal is taken out from the bio-body 7 by using the ionic reaction complex 4 and the mixed ionic polymer 5, and the electric signal is conducted to the sensor device etc. (not shown) via the conductive substrate 2. As described above, in the bio-electrode of the present invention, the ionic reaction complex 4 can be used to take into account both the conductivity and bio-compatibility, and also has adhesiveness, so the contact area with the skin is constant, and the electric signal from the skin can be stably obtained with high sensitivity.

[0386] The constituent materials of the biological electrode of the present invention are described in more detail below.

[0387] [Conductive substrate]

[0388] The biological electrode of the present invention has a conductive substrate, which is usually electrically connected to a sensor device or the like, and transmits an electrical signal extracted from the biological body through the biological contact layer to the sensor device or the like.

[0389] The conductive substrate is not particularly limited as long as it has conductivity, and preferably contains one or more selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon and a conductive polymer.

[0390] The conductive substrate is not particularly limited, and may be a hard conductive substrate, a flexible conductive film, a cloth coated with a conductive paste, or a cloth mixed with a conductive polymer. The conductive substrate may be flat, may have irregularities, or may be a mesh woven with metal wires, and may be appropriately selected according to the purpose of the biological electrode.

[0391] [Biological contact layer]

[0392] The bioelectrode of the present invention has a biocontact layer formed on a conductive substrate. This biocontact layer is the part that actually contacts the bioelectrode when the bioelectrode is used, and has conductivity and adhesiveness. The biocontact layer is a hardened product of the bioelectrode composition of the present invention, that is, an adhesive resin layer composed of a hardened product of a composition containing the above-mentioned (A) component and optionally (B), (C), (D), (E), and other (F) components.

[0393] Furthermore, the adhesion of the biological contact layer is preferably in the range of 0.5 N / 25 mm or more and 20 N / 25 mm or less. The method for measuring the adhesion is generally the method shown in JIS Z 0237. The substrate can be a metal substrate such as SUS (stainless steel) or a PET (polyethylene terephthalate) substrate, but human skin can also be used for measurement. The surface energy of human skin is lower than that of metal and various plastics, and is close to the low energy of Teflon (registered trademark), and has the property of not being easy to adhere.

[0394] The thickness of the biocontact layer of the bioelectrode is preferably 1 μm to 5 mm, and more preferably 2 μm to 3 mm. The thinner the biocontact layer, the lower the adhesion, but the flexibility is improved, and the weight is reduced, and the compatibility with the skin is improved. The thickness of the biocontact layer can be selected by comprehensively considering the adhesion and the touch to the skin.

[0395] In addition, the biological electrode of the present invention, like the previous biological electrodes (for example, the biological electrodes described in Japanese Patent Gazette No. 2004-033468), can also be provided with an adhesive film on the biological contact layer in order to prevent the biological electrode from peeling off from the biological body during use. When the adhesive film is provided, an adhesive film material such as acrylic, carbamate, or silicone can be used to form the adhesive film. In particular, silicone is ideal because of its high oxygen permeability, which allows the skin to breathe even when attached, and its high water repellency, so that the adhesion is less reduced due to sweat, and its irritation to the skin is low. In addition, the biological electrode of the present invention can be prevented from peeling off from the biological body by adding an adhesiveness imparting agent to the biological electrode composition, or by using a resin with good adhesion to the biological body, as described above, so the above-mentioned adhesive film provided separately is not necessarily required.

[0396] When the biological electrode of the present invention is used as a wearable device, there are no particular limitations on the wiring and other components between the biological electrode and the sensor device, and for example, those described in Japanese Patent Application Laid-Open No. 2004-033468 may be used.

[0397] As described above, if it is a biological electrode of the present invention, the biological contact layer is formed by the hardened material of the biological electrode composition of the present invention, so the electrical signal from the skin can be transmitted to the device with good efficiency (that is, excellent conductivity), even if it is installed on the skin for a long time, there is no risk of causing allergies (that is, excellent biological compatibility), it is lightweight, can be manufactured at low cost, and the conductivity does not drop significantly even if it is wetted by water or dried. In addition, by adding conductive powder, the conductivity can be made better, and by combining with a resin with adhesiveness and elasticity, a biological electrode with particularly high adhesiveness and high elasticity can be manufactured. In addition, additives can be used to make the elasticity and adhesion to the skin better, and the elasticity and adhesion can be adjusted by appropriately adjusting the composition of the resin and the thickness of the biological contact layer. Therefore, such a biological electrode of the present invention is particularly suitable as a biological electrode used in a medical wearable device.

[0398] <Method for producing biological electrode>

[0399] Furthermore, the present invention provides a method for manufacturing a biological electrode, which is a method for manufacturing a biological electrode having a conductive substrate and a biological contact layer formed on the conductive substrate, by coating the above-mentioned biological electrode composition of the present invention on the aforementioned conductive substrate and hardening it to form the aforementioned biological contact layer.

[0400] Furthermore, the conductive substrate and the like used in the method for producing the biological electrode of the present invention may be the same as those described above.

[0401] The method of coating the bioelectrode composition on the conductive substrate is not particularly limited, and methods such as dip coating, spray coating, spin coating, roller coating, flow coating, doctor blade coating, screen printing, flexographic printing, gravure printing, inkjet printing, etc. are suitable.

[0402] The method for curing the resin is not particularly limited, and can be appropriately selected depending on the components (A) and (B) used in the bioelectrode composition, for example, using heat or light, or using these to cure the resin is preferred. Alternatively, a catalyst that generates an acid or a base may be added to the bioelectrode composition in advance to generate a crosslinking reaction and cure the resin.

[0403] The temperature during heating is not particularly limited and can be appropriately selected depending on the components (A) and (B) used in the bioelectrode composition, and is preferably about 50 to 250°C.

[0404] When heating and irradiation are combined, heating and irradiation may be performed simultaneously, heating may be performed after irradiation, or irradiation may be performed after heating. In addition, air drying may be performed before heating after coating in order to evaporate the solvent.

[0405] If water is dripped on the surface of the hardened film, or water vapor or mist is blown, the compatibility with the skin will be improved, and biological signals can be quickly obtained. In order to make the water droplets of water vapor or mist smaller, water mixed with alcohol can also be used. The film surface can also be wetted by contacting with water-containing absorbent cotton or cloth.

[0406] The water that wets the surface of the hardened film may also contain salt. The water-soluble salt mixed with water is selected from sodium salt, potassium salt, calcium salt, magnesium salt, and betaine.

[0407] The water-soluble salt may be specifically selected from sodium chloride, potassium chloride, calcium chloride, magnesium chloride, saccharin sodium salt, acesulfame potassium, sodium carboxylate, potassium carboxylate, calcium carboxylate, sodium sulfonate, potassium sulfonate, calcium sulfonate, sodium phosphate, potassium phosphate, calcium phosphate, magnesium phosphate, and betaine. The water-soluble salt does not include the above-mentioned component (A) and component (C).

[0408] More specifically, in addition to the above, there can be mentioned sodium acetate, sodium propionate, sodium trimethylacetate, sodium glycolate, sodium butyrate, sodium valerate, sodium caproate, sodium heptanoate, sodium octanoate, sodium nonanoate, sodium decanoate, sodium undecylate, sodium laurate, sodium tridecylate, sodium myristate, sodium pentadecylate, sodium palmitate, sodium heptadecanoate, sodium stearate, sodium benzoate, disodium adipate, disodium maleate, disodium phthalate, sodium 2-hydroxybutyrate, sodium 3-hydroxybutyrate, sodium 2-oxobutyrate, sodium gluconate, sodium methanesulfonate, 1- Sodium nonanesulfonate, sodium 1-decanesulfonate, sodium 1-dodecanesulfonate, sodium 1-undecanesulfonate, sodium coconut fat base isethionate, sodium lauroyl methyl alanine, sodium coconut fat base methyl taurate, sodium coconut fat base glutamate, sodium coconut fat base, sodium lauroyl methyl taurate, lauramidopropyl betaine, potassium isobutyrate, potassium propionate, potassium trimethylacetate, potassium glycolate, potassium gluconate, potassium methanesulfonate, calcium stearate, calcium glycolate, calcium gluconate, calcium 3-methyl-2-oxobutyrate, calcium methanesulfonate. Betaine is a general term for intramolecular salts, and specifically, it is a compound in which three methyl groups are added to the amino group of an amino acid, and more specifically, trimethylglycine, carnitine, and proline betaine can be cited.

[0409] The water that wets the surface of the hardened film may further contain a monohydric alcohol or a polyhydric alcohol having 1 to 4 carbon atoms. The alcohol is preferably selected from ethanol, isopropanol, ethylene glycol, diethylene glycol, triethylene glycol, glycerol, polyethylene glycol, polypropylene glycol, polyglycerol, diglycerol, or a polysilicone compound having a polyglycerol structure. The polysilicone compound having a polyglycerol structure is more preferably represented by the above-mentioned general formula (4)' or (5)'.

[0410] The pretreatment method using an aqueous solution containing a water-soluble salt can wet the biological electrode membrane after hardening by spraying, water drop dispensing, etc. It can also be wetted in a high temperature and high humidity state like a sauna. After wetting, in order to prevent drying, a protective film can be stacked on the permeable layer to cover it. The protective film needs to be peeled off just before applying it to the skin, so a Teflon (registered trademark) film coated with a peeling agent or peelable can be used. For long-term storage, the dry electrode covered with a peeling film is preferably sealed in a bag covered with aluminum or the like. In order to prevent drying in the aluminum-covered bag, it is better to seal water in it in advance.

[0411] Before attaching the biological electrode of the present invention to the skin, the skin side may be wetted with water, alcohol, etc., or the skin may be wiped with a cloth or absorbent cotton containing water, alcohol, etc. The water or alcohol may also contain the aforementioned salt.

[0412] As described above, the method for manufacturing the biological electrode of the present invention can easily manufacture the biological electrode of the present invention at low cost, which has excellent conductivity and biocompatibility, is lightweight, and does not significantly reduce conductivity even when wetted or dried.

[0413] [Example]

[0414] The present invention will be specifically described below using Examples and Comparative Examples, but the present invention is not limited thereto. "Me" represents a methyl group, and "Vi" represents a vinyl group.

[0415] (Ionic polymer)

[0416] Ionic polymers 1 to 14, blended ionic polymer 1, and comparative ionic polymer 1, which are incorporated as ionic materials (conductive materials) in biological electrode compositions, are synthesized in the following manner. A 30% by weight cyclopentanone solution of each monomer is placed in a reaction vessel and mixed, and the reaction vessel is cooled to -70°C in a nitrogen environment, and degassing and nitrogen blowing under reduced pressure are repeated three times. After the temperature is raised to room temperature, 0.02 mol of azobisisobutyronitrile (AIBN) as a polymerization initiator is added to 1 mol of the total monomers, and the temperature is raised to 60°C, and the mixture is reacted for 15 hours. With respect to the composition of the obtained polymer, the solvent is dried and then the reaction is performed using 1 H-NMR was used to confirm. The molecular weight (Mw) and the degree of dispersion (Mw / Mn) of the obtained polymer were confirmed by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent. The ionic polymers 1 to 14, blended ionic polymer 1, and comparative ionic polymer 1 synthesized in this manner are shown below.

[0417] Ionic polymer 1

[0418] Mw=38,800

[0419] Mw / Mn=1.91

[0420] [Chemistry 88]

[0421]

[0422] Ionic polymer 2

[0423] Mw=24,600

[0424] Mw / Mn=1.85

[0425] [Chemistry 89]

[0426]

[0427] Ionic polymer 3

[0428] Mw=54,300

[0429] Mw / Mn=1.95

[0430] [Chemistry 90]

[0431]

[0432] Ionic polymer 4

[0433] Mw=25,500

[0434] Mw / Mn=1.89

[0435] [Chemistry 91]

[0436]

[0437] The number of replicates in the formula represents the average value.

[0438] Ionic polymer 5

[0439] Mw=23,100

[0440] Mw / Mn=1.61

[0441] [Chemistry 92]

[0442]

[0443] Ionic polymer 6

[0444] Mw=16,400

[0445] Mw / Mn=1.98

[0446] [Chemistry 93]

[0447]

[0448] Ionic polymer 7

[0449] Mw=42,100

[0450] Mw / Mn=2.11

[0451] [Chemistry 94]

[0452]

[0453] The number of replicates in the formula represents the average value.

[0454] Ionic polymer 8

[0455] Mw=19,800

[0456] Mw / Mn=1.91

[0457] [Chemistry 95]

[0458]

[0459] The number of replicates in the formula represents the average value.

[0460] Ionic polymer 9

[0461] Mw=21,300

[0462] Mw / Mn=2.05

[0463] [Chemistry 96]

[0464]

[0465] The number of replicates in the formula represents the average value.

[0466] Ionic polymer 10

[0467] Mw=22,400

[0468] Mw / Mn=1.74

[0469] [Chemistry 97]

[0470]

[0471] Ionic polymer 11

[0472] Mw=26,600

[0473] Mw / Mn=1.99

[0474] [Chemistry 98]

[0475]

[0476] Ionic polymer 12

[0477] Mw=21,500

[0478] Mw / Mn=1.75

[0479] [Chemistry 99]

[0480]

[0481] Ionic polymer 13

[0482] Mw=22,100

[0483] Mw / Mn=1.69

[0484] [Chemical 100]

[0485]

[0486] The number of replicates in the formula represents the average value.

[0487] Ionic polymer 14

[0488] Mw=24,500

[0489] Mw / Mn=1.64

[0490] [Chemistry 101]

[0491]

[0492] The number of replicates in the formula represents the average value.

[0493] Ionic polymer 15

[0494] Mw=44,800

[0495] Mw / Mn=1.99

[0496] [Chemistry 102]

[0497]

[0498] The number of replicates in the formula represents the average value.

[0499] Ionic polymer 16

[0500] Mw=48,600

[0501] Mw / Mn=1.96

[0502] [Chemistry 103]

[0503]

[0504] The number of replicates in the formula represents the average value.

[0505] Ionic polymer 17

[0506] Mw=62,600

[0507] Mw / Mn=1.99

[0508] [Chemistry 104]

[0509]

[0510] The number of replicates in the formula represents the average value.

[0511] The blended ionic polymer 1 and the comparative ionic polymer 1 used in the comparative example are shown below.

[0512] Blended ionic polymer 1

[0513] Mw=39,100

[0514] Mw / Mn=1.91

[0515] [Chemistry 105]

[0516]

[0517] The number of replicates in the formula represents the average value.

[0518] Comparative Ionic Polymer 1

[0519] Mw=26,900

[0520] Mw / Mn=1.99

[0521] [Chemistry 106]

[0522]

[0523] (Composite carbon particles)

[0524] To 100 g of methyl isobutyl ketone (MIBK), add 5 g of carbon black: DENKABLACK Li-400 manufactured by Denka Co., Ltd. and 1 g of pyridine and stir, to which 5 g of a 30 wt % concentration cyclopentanone solution of ionic polymer 1 is added dropwise, and after stirring at 60 °C for 20 hours, the solvent is dried to synthesize ionic polymer 1 composite carbon black.

[0525] In the same manner, ionic polymer 2 composite carbon black to ionic polymer 13 composite carbon black, ionic polymer 15 composite carbon black, ionic polymer 16 composite carbon black, ionic polymer 17 composite carbon black and ionic polymer 1 composite carbon black were synthesized for comparison.

[0526] To 100 g of methyl isobutyl ketone (MIBK), add 5 g of carbon black: DENKABLACK Li-400 manufactured by Denka Co., Ltd. and stir. To this is added dropwise 5 g of a 30 wt % concentration cyclopentanone solution of ionic polymer 14 and 0.01 g of tributyltin. After stirring at 600° C. for 20 hours, the solvent is dried to synthesize ionic polymer 14 composite carbon black.

[0527] 5 g of carboxylated multilayer carbon nanotubes (SIGMA-Aldrich) and 1 g of pyridine were added to 100 g of methyl isobutyl ketone (MIBK) and stirred. 5 g of 30 wt% cyclopentanone solution of ionic polymer 8 was added dropwise thereto. After stirring at 60° C. for 20 hours, the solvent was dried to synthesize ionic polymer 8 composite carbon nanotubes.

[0528] 5 g of graphene oxide (SIGMA-Aldrich) and 1 g of pyridine were added to 100 g of methyl isobutyl ketone (MIBK), and the mixture was stirred. 5 g of a 30 wt% cyclopentanone solution of ionic polymer 8 was added dropwise thereto. After stirring at 60° C. for 20 hours, the solvent was dried to synthesize ionic polymer 8 composite graphene.

[0529] 5 g of graphite (SIGMA-Aldrich, size less than 20 μm) and 1 g of pyridine were added to 100 g of methyl isobutyl ketone (MIBK), and the mixture was stirred. 5 g of a 30 wt% cyclopentanone solution of ionic polymer 8 was added dropwise thereto. After stirring at 60 °C for 20 hours, the solvent was dried to synthesize ionic polymer 8 composite graphite.

[0530] The following are the siloxane compounds 1 to 4 as polysiloxane-based resins blended into the bioelectrode composition solution.

[0531] (Siloxane compound 1)

[0532] The viscosity of the 30% toluene solution is 27,000 mPa·s, the olefin content is 0.007 mol / 100 g, and the molecular chain ends are SiMe 2 As the siloxane compound 1, a vinyl-containing polydimethylsiloxane terminated with a Vi group was used.

[0533] (Siloxane compound 2)

[0534] Will be by Me 3 SiO 0.5 Unit and SiO 2 MQ resin polysiloxane (Me 3 SiO 0.5 Unit / SiO 2 Unit = 0.8) was prepared as a 60% toluene solution of Siloxane Compound 2.

[0535] (Siloxane compound 3)

[0536] The viscosity of the 30% toluene solution is 42,000 mPa·s, the alkenyl content is 0.007 mol / 100 g, 40 parts by mass of vinyl-containing polydimethylsiloxane with OH-terminated molecular chain ends, and Me 3 SiO 0.5 Unit and SiO 2 MQ resin polysiloxane (Me 3 SiO 0.5 Unit / SiO 2 A solution consisting of 100 parts by mass of a 60% toluene solution of 1,2-dimethylsiloxane (1,2-dimethylsiloxane) and 26.7 parts by mass of toluene was heated for 4 hours under dry distillation and then cooled to bond polydimethylsiloxane to the MQ resin, thereby obtaining Siloxane Compound 3.

[0537] (Siloxane compound 4)

[0538] As the methyl hydrogen polysilicone oil, KF-99 manufactured by Shin-Etsu Chemical Co., Ltd. was used.

[0539] The polyglycerol polysiloxane compounds 1 to 7 (polyglycerol compounds) are shown below.

[0540] [Chemistry 107]

[0541]

[0542] The organic solvents blended into the bioelectrode composition solution are as follows.

[0543] ISOPARG: Isoparaffin solvent standard petroleum

[0544] ISOPARM: Isoparaffin solvent standard petroleum

[0545] The lithium titanate powder, platinum catalyst, and conductivity enhancer (carbon black, carbon nanotubes, metal powder) mixed as additives in the bioelectrode composition solution are shown below.

[0546] Metal powder Silver powder: Silver flakes made by Sigma-Aldrich, diameter 10 μm

[0547] Lithium titanate powder, spinel: manufactured by Sigma-Aldrich, size less than 200nm

[0548] Platinum catalyst: Shin-Etsu Chemical Co., Ltd., CAT-PL-50T

[0549] Carbon black: Denka Black Li-400 manufactured by Denka Corporation

[0550] Multilayered carbon nanotubes: manufactured by Sigma-Aldrich, with a diameter of 110-170 nm and a length of 5-9 μm

[0551] [Examples 1 to 20, Comparative Examples 1 to 3]

[0552] According to the composition recorded in Tables 1 and 2, ionic polymer composite carbon particles, resin, blended ionic polymer, organic solvent, and additives (platinum catalyst, conductivity enhancer, etc.) are mixed to prepare biological electrode composition solutions (biological electrode composition solutions 1 to 20, comparative biological electrode composition solutions 1 to 3).

[0553] [Table 1]

[0554]

[0555] [Table 2]

[0556]

[0557] (Fabrication of biological electrodes)

[0558] like Figure 3 , on the ST-604 thermoplastic urethane (TPU) film 20 of Bemis, the conductive paste DOTITE FA-333 manufactured by Fujikura Chemical was applied by screen printing, and baked in an oven at 120I for 10 minutes to print a keyhole-shaped conductive pattern 2 with a circular diameter of 2 cm. The bioelectrode composition solution described in Tables 1 and 2 was applied by screen printing to the circular part overlapping the conductive pattern, air-dried at room temperature for 10 minutes, and then baked in an oven at 125 for 10 minutes to evaporate the solvent and harden it to form a biocontact layer 3, thereby obtaining a bioelectrode 1. Then, as Figure 4 As shown, the thermoplastic urethane film 20 on which the biological electrode 1 is printed is cut and a double-sided tape 21 is attached thereto, thereby preparing three biological electrode samples 10 with respect to one component solution.

[0559] (Measurement of the thickness of the biocontact layer)

[0560] The thickness of the bioelectrode layer in the bioelectrode produced above was measured using a micrometer.

[0561] (Measurement of biological signals)

[0562] The conductive wiring pattern of the biological electrode obtained by using the conductive paste is connected to the portable electrocardiograph HCG-901 manufactured by Omron Healthcare Corporation with a conductive wire, and the positive electrode of the electrocardiograph is attached to the Figure 5The negative electrode is attached to the LA of the human body, the negative electrode is attached to the LL, and the ground electrode is attached to the RA. After attaching, the electrocardiogram is measured and the measurement is performed until Figure 6 The results of the electrocardiogram waveform (ECG signal) composed of P, Q, R, S, and T waves are shown in Table 3.

[0563] [Table 3]

[0564]

[0565] As shown in Table 3, Examples 1 to 20 in which the biocontact layer was formed using the bioelectrode composition of the present invention in which the composite of the ionic polymer and the carbon particles was mixed, could obtain biosignals in a short time after being attached to the body. On the other hand, in the case of adding only carbon particles and in the case of Comparative Examples 1 and 3 which did not contain the ionic component of the specific structure, no biosignals could be obtained. Comparative Example 2 in which only the ionic polymer was added took a long time from attachment to the skin to the expression of the biosignal.

[0566] As described above, if a bioelectrode having a biocontact layer formed using the bioelectrode composition of the present invention is used, it has excellent conductivity, biocompatibility, adhesion to a conductive substrate, and high ion conductivity, and can thus obtain a biosignal immediately after being attached to the skin.

[0567] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and those having substantially the same structure and exerting the same functions and effects as the technical concept described in the claims of the present invention are all included in the technical scope of the present invention.

[0568] [Description of Reference Numerals]

[0569] 1: Biological Electrode

[0570] 2: Conductive substrate (conductive pattern)

[0571] 3: Bio-contact layer

[0572] 4: Ionic reaction complex

[0573] 5: Blending with ionic polymers

[0574] 6: Adhesive resin

[0575] 7: Organisms

[0576] 10: Biological electrode samples

[0577] 20: Thermoplastic urethane film

[0578] 21: Double-sided tape

[0579] LA: positive electrode attachment

[0580] LL: Negative electrode attachment

[0581] RA: Grounding attachment

Claims

1. A biological electrode composition comprising (A) a reaction complex of an ionic polymer material and carbon particles, wherein the (A) component comprises carbon particles chemically bonded to a polymer having a repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt, or silver salt selected from any one of fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide, and the biological electrode composition further comprises an adhesive resin as the (B) component, and the blending amount of the (A) component is 1 to 200 parts by mass relative to 100 parts by mass of the (B) component.

2. The biological electrode composition according to claim 1, wherein: The carbon particles are selected from carbon black, carbon nanotubes, graphite and graphene.

3. The biological electrode composition according to claim 1 or 2, wherein: The repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt, or silver salt selected from fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide has a structure represented by any one of the following general formulas (1)-1 to (1)-4; In the formula, Rf1 and Rf2 are hydrogen atoms, fluorine atoms, oxygen atoms, methyl groups, or trifluoromethyl groups. When Rf1 and Rf2 are oxygen atoms, Rf1 and Rf2 are oxygen atoms bonded to one carbon atom to form a carbonyl group. Rf3 and Rf4 are hydrogen atoms, fluorine atoms, or trifluoromethyl groups, and one or more of Rf1 to Rf4 are fluorine atoms or trifluoromethyl groups. Rf5, Rf6, and Rf7 are fluorine atoms, linear or branched alkyl groups having 1 to 4 carbon atoms, and have at least one fluorine atom; m is an integer from 1 to 4; M + The ion is selected from ammonium ion, lithium ion, sodium ion, potassium ion and silver ion.

4. The biological electrode composition according to claim 1 or 2, wherein: The repeating unit having a structure of an ammonium salt, lithium salt, sodium salt, potassium salt or silver salt selected from any one of fluorosulfonic acid, fluorosulfonyl imide and N-carbonyl fluorosulfonamide is selected from at least one of the repeating units a1 to a7 described in the following general formula (2); In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 Each independently represents a single bond, or may have an ester group or an ether group, or both, and is any one of a linear, branched, or cyclic hydrocarbon group having 1 to 13 carbon atoms; R 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, and R 7 One or two of the hydrogen atoms in the fluorine atom may also be substituted by a fluorine atom; X1, X2, X3, X4, X6, and X7 are each independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group; X5 is a single bond, an ether group, or an ester group; Y is an oxygen atom, -NR 19 -Base, R 19 is a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and may be 4 Bond to form a ring; m is an integer from 1 to 4; a1, a2, a3, a4, a5, a6 and a7 are 0≤a1≤1.0, 0≤a2≤1.0, 0≤a3≤1.0, 0≤a4≤1.0, 0≤a5≤1.0, 0≤a6≤1.0, 0≤a7≤1.0, 0<a1+a2+a3+a4+a5+a6+a7≤1.0; M + is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion; Rf5, Rf6, and Rf7 are fluorine atoms, linear or branched alkyl groups having 1 to 4 carbon atoms, and have at least one fluorine atom.

5. The biological electrode composition according to claim 4, wherein: The component (A) comprises a composite obtained by reacting a polymer reactive with carbon particles, in which a repeating unit b1 having an oxirane group or an oxetane group or a repeating unit b2 having an isocyanate group of the following general formula (4) is copolymerized in addition to the repeating unit of the general formula (2) and carbon particles; In the formula, R 20 , R 24 is a hydrogen atom or a methyl group, X8 is a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, X9 is an ester group, and R 21 It is a single bond, a linear, branched, or cyclic alkylene or phenylene group having 1 to 20 carbon atoms, and may also contain an ether group, an ester group, or a hydroxyl group; R 22 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, which may be the same or different. 21 Bond and form rings; R 23 For methylene, ethylene, and can also be 21 Bond and form rings; R 25 A linear or branched alkylene group having 1 to 20 carbon atoms, which may also have an ether group; R 26 is a single bond or a methylene group; B is an isocyanate group, which may also be a blocked isocyanate group; 0≤b1<1.0, 0≤b2<1.0, 0<b1+b2<1.

0.

6. The biological electrode composition according to claim 1 or 2, wherein: The component (A) is obtained by reacting 5 parts by mass or more of a polymer that reacts with the carbon particles with respect to 100 parts by mass of the carbon particles.

7. The biological electrode composition according to claim 1 or 2, wherein: The component (A) contains ammonium ions represented by the following general formula (3) as ammonium ions constituting the ammonium salt; In the formula, R 101d , R 101e , R 101f , R 101g Each of them is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 13 carbon atoms, a linear, branched, or cyclic alkenyl or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more selected from an ether group, a carbonyl group, an ester group, a hydroxyl group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom; R 101d With R 101e , R 101d With R 101e With R 101f They can also form a ring with the nitrogen atom to which they are bonded. When forming a ring, R 101d With R 101e and R 101d With R 101e With R 101f It is an alkylene group having 3 to 10 carbon atoms, or a heteroaromatic ring having a nitrogen atom in the ring.

8. The biological electrode composition according to claim 1, wherein: The component (B) is at least one selected from silicone resins, (meth)acrylate resins, and urethane resins.

9. The biological electrode composition according to claim 1, wherein: The component (B) contains a diorganosiloxane having an alkenyl group and an organohydrogenpolysiloxane having a SiH group.

10. The biological electrode composition according to claim 9, wherein: The component (B) further contains x SiO (4-x) / 2 The polysilicone resin comprises SiO2 units, R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.

5.

11. The bioelectrode composition according to claim 1 or 2, further comprising a polymer compound having ionic repeating units as component (C).

12. The biological electrode composition according to claim 11, wherein: The ionic repeating unit of the component (C) comprises a repeating unit of the following general formula (2) having a structure selected from any one of ammonium salts, lithium salts, sodium salts, potassium salts, and silver salts of fluorosulfonic acid, fluorosulfonyl imide, and N-carbonyl fluorosulfonamide; In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 Each independently represents a single bond, or may have an ester group or an ether group, or both, and is any one of a linear, branched, or cyclic hydrocarbon group having 1 to 13 carbon atoms; R 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 One or two of the hydrogen atoms in the fluorine atom may also be substituted by a fluorine atom; X1, X2, X3, X4, X6, and X7 are each independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group; X5 is a single bond, an ether group, or an ester group; Y is an oxygen atom, -NR 19 -Base, R 19 is a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, and may be 4 Bond to form a ring; m is an integer from 1 to 4; a1, a2, a3, a4, a5, a6 and a7 are 0≤a1≤1.0, 0≤a2≤1.0, 0≤a3≤1.0, 0≤a4≤1.0, 0≤a5≤1.0, 0≤a6≤1.0, 0≤a7≤1.0, 0<a1+a2+a3+a4+a5+a6+a7≤1.0; M + is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion; Rf5, Rf6, and Rf7 are fluorine atoms, linear or branched alkyl groups having 1 to 4 carbon atoms, and have at least one fluorine atom.

13. The biological electrode composition according to claim 1 or 2, further comprising carbon powder and / or metal powder as component (D).

14. The biological electrode composition according to claim 13, wherein: The carbon powder is any one or more of carbon black, graphite and carbon nanotubes.

15. The biological electrode composition according to claim 13, wherein: The metal powder is selected from gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium and indium.

16. The biological electrode composition according to claim 15, wherein: The metal powder is silver powder.

17. The bioelectrode composition according to claim 1 or 2, further comprising an organic solvent as component (E).

18. A biological electrode comprising a conductive substrate and a biological contact layer formed on the conductive substrate, characterized in that: The living body contact layer is a hardened material of the living body electrode composition according to any one of claims 1 to 17.

19. The biological electrode according to claim 18, wherein: The conductive substrate contains one or more selected from the group consisting of gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and a conductive polymer.

20. A method for manufacturing a bioelectrode, comprising: a conductive substrate and a biocontact layer formed on the conductive substrate; and exist The bio-electrode composition according to any one of claims 1 to 17 is coated on the conductive substrate and cured to form the bio-contact layer.

21. The method for producing a biological electrode according to claim 20, wherein the conductive substrate contains one or more selected from the group consisting of gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and a conductive polymer.